The Place of Pulses in India With Particular Reference to the Arid Zones - Mann, H S; Singh, Panjab (Annals of Arid Zone, 2016)
Th. possibility of alleviating India's food protein deficiency through the propagation of high-yielding pulse crops with the aid of the indigenously developed improved production technology has been discussed. The need for vigorous extension efforts at this stage, rather than further research, in the field of pulse crop production has been emphasised. The importance of the arid and semi-arid regions in this context has been highlighte